Handbook of molecular and cellular methods in biology and medicine - Cseke, Leland J. (Boca Raton : CRC Press/Taylor & Francis Group, 2011)
"Reflecting the milestones in the field that have occurred since the publication of the first edition, this book provides an updated tool kit that incorporates conventional as well as modern approaches to tackling biological and medicinal research in the post genomic era. The authors have evaluated, revised, and sometimes replaced all protocols with more efficient, reliable, or simpler ones. The book is also completely reorganized and covers topics of modern "omics" approaches, including genomics, proteomics, and metabolomics. This is followed coverage of the Manipulation of Biological Systems, including RNAi, and the use of microscopy"--Provided by publisher.
pt. 1. DNA-based technology -- pt. 2. RNA-based technology -- pt. 3. Protein-based technology -- pt. 4. Metabolites -- pt. 5. Genomics, proteomics, and metabolomics -- pt. 6. Manipulation of biological systems -- pt. 7. Macromolecular analyses.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Molecular biology -- Laboratory manuals; Cytology -- Laboratory manuals; Electronic books